Agency and Violence: An African Philosophical Approach - Villet, Charles M.; Sanni, John S. (African studies (Johannesburg), 2025)
The articles in this special issue of African Studies were selected from papers and presentations presented at a conference on the theme 'Agency and Violence: An African Philosophical Approach' the philosophy department at the University of Pretoria hosted in 2023. Thought-provoking discussion and debate on a theme that is controversial but crucial within the African context and more broadly in the Global South characterised the small but lively conference. This special issue aims to engage with varying contexts across the continent where violence is a daily reality. This theme was the brainchild of John Sanni and the regular conversations that he and Charles Villet had in the years preceding the conference. Their academic partnership focuses on themes regarding violence, and it became clear in their own research that violence is not just a passive phenomenon that impacts the livelihood of ordinary citizens on the ground (although this is certainly the case for a great deal of people) but also an active response to oppression and the spectre of colonialism that still exists in society.